Digital localization of intraoperative samples enhances margin analysis precision in oral squamous cell carcinoma - Michcik, Adam; Ciarka, Aleksandra; Garbacewicz, Łukasz; Polcyn, Adam; Choma, Piotr; Wojciechowska, Barbara; Drogoszewska, Barbara (Frontiers in Medicine, 2025)
ObjectivesThe intraoperative margin assessment technique enhances local control of Oral Squamous Cell Carcinoma (OSCC). However, the standard frozen section analysis (FSA) procedure does not allow precise interpretation of the final histopathological results. For this reason, we have developed a modified intraoperative margins (IM) assessment protocol using virtual 3D images of resected OSCC.Material and methodsThe pilot study included 10 patients with OSCC located in the floor of the mouth (FOM, n = 3), tongue (TC, n = 2), maxilla (MT, n = 1), and retromolar triangle (RMT, n = 4). After excision, OSCCs were scanned and mapped, marked on the virtual preparation of the IM collection sites. The modified pathological assessment of the IM enabled the evaluation of dimensions, including the width of the collected IM.ResultsBy analyzing virtual OSCC images, we demonstrated the effectiveness of a modified IM assessment methodology. In one case study, the oncological council disqualified the patient from adjuvant radiotherapy.ConclusionLeveraging the OSCC’s virtual mapping capabilities and the modified IM pathology methodology, we developed an IM evaluation protocol that enables the incorporation of IM width into the OSCC’s microscopic excision margin, thereby significantly enhancing the diagnostic value and precision of the final OSCC histopathology results.